Fire safety knowledge and awareness among budget hotel guests - Nadila Syakira, Zohari (2025)
Fire safety within budget hotels is essential, especially for guest and staff safety and well-being. This paper examines the factors influencing fire safety knowledge and awareness among budget hotel guests. The first aim of this study are to assess the fire safety knowledge and awareness levels of budget hotel guests. Following that, to identify the factor that influence the fire safety knowledge and awareness, and lastly, to determine the relationship between fire safety knowledge and awareness and its associated factors among budget hotel guests. A cross-sectional study was conducted involving 62 budget hotel guests located at Pekan, Pahang. Convenience sampling was used for distribution of questionnaire to the respondents in a month duration. The questionnaire comprises 46 questions. The collected data were then analysed using Statistical Packages for Social Science (SPSS) version 25.0. Majority of the respondents were male (85.5%), aged 21-39 years old (74.2%), ethnicity of Malay (66.1%) and tertiary level of education (71.0%). 53.2% respondents has moderate level of fire safety knowledge and 45.2% demonstrates good level of awareness. Guests that attended fire safety course were most significantly has higher level of knowledge of fire safety (X²=37.374, p-value=0.015) compared to those who did not. A significant moderate positive correlation (r = 0.567, p < 0.001) was found between fire safety knowledge and awareness among respondents, indicating that higher levels of fire safety knowledge are associated with increased awareness. Overall, Companies and educational institutes are recommended to conduct regular fire safety drills and provide fire safety courses to improve the level of fire safety knowledge and awareness.